Fiber-Enhanced Raman Spectroscopy for Trace-Gas Sensing in the High-Concentration Gas Background With an Anti-Resonant Hollow Core Fiber - Qian, Guochao; Wan, Fu; Zhou, Feng; Wang, Jianxin; Kong, Weiping; Chen, Weigen (Frontiers in Physics, 2022)
In this paper, with an anti-resonant hollow core fiber (ARHCF), fiber-enhanced Raman spectroscopy(FERS) for trace-gas sensing in high-concentration gas background is demonstrated for the first time. The performance of the apparatus is verified by detecting trace-gas in the high concentration SF6 and gaseous impurities in the high concentration C2H6. With a 1.5 W laser source and 60 s exposure time, limit of detection (LOD) of gases at tens of ppm level are achieved, including carbonyl sulfide (COS), carbon tetrafluoride (CF4), carbon dioxide (CO2), carbon monoxide (CO), methane (CH4), acetylene (C2H2), ethylene (C2H4), propyne (C3H4), propylene (C3H6), and propane (C3H8). Quantification of multigas with great accuracy exceeding 94% is also realized. It shows that the FERS can realize multigas sensing with high selectivity, sensitivity, and accuracy, which is meaningful.